Dialect Words in the Novel-Ballad “Blue Chamois” by M. Nesterchuk”. Part I (Linguostylistic Studies, 2019)
The article highlights usage of the dialect words in the novel-ballad Blue Chmois written by M. Nesterchuk who is a native of the village Sylno, Kivertsi district, Volyn region. The residents of this village have become the writer's prototypes for the characters of his novel, and they all use the words of the local dialect in their communication. The dialect of the village of Sylno comprises the features of two dialects – the Western and Middle Polissia, with a clear predominance of the Middle Polissian dialect phonetic features.The study focuses on the use of two types of dialectisms – phonetic and word-forming. The case study has revealed the topping dialectal features which the writer prefers in his characters' speech, having compared them with a local dialect. The novel reflects the following features of vocalism: у instead of о in closed syllabl (туй, Забур’я, Запулля), convergence of the unstressed e with и (ни вони, чирвониї) and others. In consonantism, we observe frequent use of prosthetic г (гоко, гонучка), replacement of ф by a sound combination хв (хвамілія, хвігура, хвундамент), pronouncing й as soft н’ and л’ (здоровля, мнясо), and others. Truncations (shortening) of the frequently used words are quite widely represented: дікалон< одекалон (apheresis) бало< бувало, тра< треба (syncopation), зара ˂ зараз, нічо< нічого (apocopa).The study has also revealed that most differences in word-forming suffixes are due to the phonetic features of the dialect, cf.: батейко, коничейко, матюнка, густющий. The writer also uses derivatives, the word-forming stems of which have been lost, cf. стриєшний ǀǀ стринешний ‘cousin (the lexeme ‘стрий‘(uncle) is no longer used in Polissian dialects), вредний (disobedient; the one who does harm/damage), (lexeme вред is no longer used).The key findings of the study argue that the author of the novel does not blindly copy the dialect but conducts a careful selection of the most common local dialect words, bringing them closer to the common folk forms.
Keywords: local dialectisms; West Polissian and Middle Polissian dialects; vocalism; consonantism; phonetic and word-forming dialectisms